Uptake of Knowledge and Technologies for Adaptation to Climate Change in Crop Production Systems in Uganda: A Review - Tenywa, John Stephen; Nabasirye, Margaret; Twinomuhangi, Revocatus; Mfitumukiza, David. (Advances in Research, 2017)
Knowledge and technology uptake in the context of climate change adaptation is critical in ensuring that communities vulnerable to climate risks, respond effectively with appropriate actions, and particularly to its extreme events that are increasingly bedeviling agricultural natural resources and livelihoods, especially in Sub-Saharan Africa. Uptake as a subject is either loosely treated or lightly understood by actors in the African climate change research and development continuum. The objective of this article was to appraise the status of uptake of innovations (knowledge and technologies) of climate change adaptations in crop-based systems in Uganda, and propose viable interventions for enhancing the uptake process to obviate the escalating effects of climate change and its associated variability. The study was conducted during December 2016. It was dominantly a desk review, primarily based on existing online information sources and other national institutional repositories. The other information source was from a two-days stakeholder workshop involving key actors within the climate change research and development value chain in Uganda. They validated the synthesised information and supplemented with more recent events and hitherto undocumented scenarios. The study revealed that uptake of climate change adaptation actions was measurably low in the country; hence, communities were far from ready to face the recurrently changing and increasingly aggressive climate change events. Among the major contributors to slow uptake were lack of a coherent climate change activity coordination entity in the country, to organise actors into a functional service delivery system with minimum duplication; ensuring quality actions and following a unidirectional long term goal. The other hindrances included scattered knowledge and technologies, sub-optimal communication and extension services, technology products misconception, low adaptation capacity, unfavourable policies and policy environments, ineffectiveness traditional public and civil society extension agencies. Interventions are proposed to obviate these bottlenecks, using largely internal mechanisms.
Keywords: Rain-fed agriculture vulnerability information communication food insecurity